Predictive simulation of physiological responses for swimmers in cold water - Yermakova, I.; Montgomery, L. D. (2018 IEEE 38th International Conference on Electronics and Nanotechnology (ELNANO): conference proceedings, 2018)
Background. Water temperature is a key consideration for swimmers` safety during competition. Besides mandatory regulations, there is generally no advice given regarding the wearing of wetsuits. Aim. This study focuses on predictive modeling of the physiological responses of competitive swimmers under challenging water temperatures as a function of swim speed, for wearing and not wearing wetsuits. The modeling approach is considered to reflect conditions typical of triathlon competition. Results. Modeling has enabled us to make quantitative evaluations of (1) thermal responses of swimmers in terms of dynamic changes of core and skin temperature, (2) heat flow as a result of skin blood flow, (3) heat production during swimming and (4) heat losses by water convection. Modeling showed that swim speed significantly affects the physiological responses of swimmers wearing and not wearing wetsuits at a water temperature of 14°C. For swimmers without wetsuits, there is a loss of swim speed and cooling of the swimmer occurs, reflecting the fact that heat loss by water convection is greater than heat production due to the physical exercise. For swimmers with wetsuits, there is an increase in swim speed, with a danger of hyperthermia because heat production due to swimming is greater than the heat loss by water convection. Conclusion. Given the potential for adverse health effects of cool water conditions on swimmers, predictive modeling that takes account of water temperature, swim speed, distance and thermo-isolation properties of the wetsuit should be carried out.